2019
DOI: 10.1182/blood-2019-124280
|View full text |Cite
|
Sign up to set email alerts
|

Liver-Directed AAV Gene Therapy for Gaucher Disease

Abstract: Introduction: Gaucher disease (GD), one of the most common lysosomal storage disorders, is an autosomal recessive condition resulting from mutations in the GBA gene that codes for the b-glucocerebrosidase (GCase) enzyme. Over 90% of patients have type 1 GD, which is characterised by lipid engorged macrophages (known as Gaucher cells) in multiple organs, including spleen, liver and bone marrow, with no overt involvement of the central nervous system (CNS). The current standard of care for type 1 GD patients inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This approach was successful in rescuing a mouse model of Pompe disease following systemic delivery of an AAV8 vector that expressed an engineered acid-α-glucosidase protein secreted by hepatocytes [ 168 ]. Freeline Therapeutics has recently used both AAV8 and novel capsid AAVS3 to deliver a GBA vector to cells and mice in a proof-of-concept study, supporting the development of a liver-directed therapy for Gaucher disease [ 169 ]. In addition, liver-specific promoters have been designed to further improve efficacy and safety, as demonstrated in pre-clinical studies in Fabry disease [ 170 , 171 ], Gaucher disease [ 172 ] and Pompe disease [ 173 , 174 ] mouse models.…”
Section: In Vivo Gene Therapymentioning
confidence: 99%
“…This approach was successful in rescuing a mouse model of Pompe disease following systemic delivery of an AAV8 vector that expressed an engineered acid-α-glucosidase protein secreted by hepatocytes [ 168 ]. Freeline Therapeutics has recently used both AAV8 and novel capsid AAVS3 to deliver a GBA vector to cells and mice in a proof-of-concept study, supporting the development of a liver-directed therapy for Gaucher disease [ 169 ]. In addition, liver-specific promoters have been designed to further improve efficacy and safety, as demonstrated in pre-clinical studies in Fabry disease [ 170 , 171 ], Gaucher disease [ 172 ] and Pompe disease [ 173 , 174 ] mouse models.…”
Section: In Vivo Gene Therapymentioning
confidence: 99%
“…Miranda et al reported promising results regarding liver-directed gene therapy in vitro and in vivo for the treatment of GD. Liver-directed GBA AAV vector administration resulted in a sustained elevation of glucocerebrosidase in the bloodstream and a higher level of its bioavailability for uptake into macrophages than with ERT (velaglucerase alfa) [ 74 ].…”
Section: Treatment Of Lysosomal Diseases Regarding Liver Involvementmentioning
confidence: 99%
“…167 Preclinical studies have shown efficacy in liverdirected gene transfer for lysosomal storage diseases (LSDs) such as Gaucher disease, Fabry disease, and glycogen storage disease type Ib and II. [169][170][171][172] LSDs are mostly monogenic and include more than 40 different metabolic diseases. The spectrum of disease severity also spans from disorders in the central nervous system (CNS) to systemic multi-organ pathology, as the enzymes are ubiquitously expressed.…”
Section: Administrationmentioning
confidence: 99%